A Unified Experimental/Theoretical Description of the Ultrafast Photophysics of Single and Double Thionated Uracils. Issue 1 (10th December 2019) - Teles‐Ferreira, Danielle Cristina; Conti, Irene; Borrego‐Varillas, Rocío; Nenov, Artur; Van Stokkum, Ivo H. M.; Ganzer, Lucia; Manzoni, Cristian; de Paula, Ana Maria; Cerullo, Giulio; Garavelli, Marco
Abstract: Photoinduced processes in thiouracil derivatives have lately attracted considerable attention due to their suitability for innovative biological and pharmacological applications. Here, sub‐20 fs broadband transient absorption spectroscopy in the near‐UV are combined with CASPT2/MM decay path calculations to unravel the excited‐state decay channels of water solvated 2‐thio and 2, 4‐dithiouracil. These molecules feature linear absorption spectra with overlapping ππ* bands, leading to parallel decay routes which we systematically track for the first time. The results reveal that different processes lead to the triplet states population, both directly from the ππ* absorbing state and via the intermediate nπ* dark state. Moreover, the 2, 4‐dithiouracil decay pathways is shown to be strongly correlated either to those of 2‐ or 4‐thiouracil, depending on the sulfur atom on which the electronic transition localizes. Abstract : Competitive decay paths for solvated thiouracils were probed with sub‐20 fs broadband transient absorption spectra and QM/MM calculations. Common features were identified: 1) the population of the triplet manifold occurs through either a direct ππ*/3nπ* ISC process or a singlet nπ* intermediate state; 2) the triplet formation occurs on a 100 fs timescale; 3) the dithionated uracil photoinduced dynamics display features of both monothionated uracils.